ARBITRATION IN SCHOOL SPORT CONTEXT: PERCEPTION OF VIOLENCE REPORTED BY REFEREES - João Carlos Martins Bressan; Kleber Tuxen Carneiro; Viviane Teixeira Silveira; Dominique Stefany Gomes dos Santos; Riller Silva Reverdito (Journal of Physical Education)
ABSTRACT The role of managing the game environment places the referee in a prominent position in sport. However, in the sport context, arbitration is highly exposed to violence.Referees occupy a prominent position in sport, having the responsibility to manage the game, and are therefore exposed to violence episodes. Research addressing violence in school competitions is still incipient; thus, the objective of this study was to identify the violence perceived by referees in youth school games. A qualitative exploratory study was performed in the state games held in 2016 in the state of Mato Grosso. The study surveyed 19 referees of categories a and b. The interviews were recorded using a digital recorder (SonyⓇ icd-px312) and the content was analyzed using software nvivoⓇ10. The results revealed that all referees have witnessed or been victims of different types of violence, confirming the fragility of the violence control system, which attributes exclusively to the referee the responsibility to manage the competition environment. Addressing the referee’s role as a content in the sport youth formation would largely contribute to the development of sport education.